2022
DOI: 10.3390/jmse10020285
|View full text |Cite
|
Sign up to set email alerts
|

Course Control of a Manta Robot Based on Amplitude and Phase Differences

Abstract: Due to external interference, such as waves, the success of underwater missions depends on the turning performance of the vehicle. Manta rays use two broad pectoral fins for propulsion, which provide better anti-interference ability and turning performance. Inspired by biological yaw modes, we use the phase difference between the pectoral fins to realize fast course adjustment and the amplitude difference to realize precise adjustment. We design a bionic robot with pectoral fins and use phase oscillators to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…At the same time, it is defined as the pectoral fin flapping mode when the space asymmetry coefficient α i line R i is not equal to 0, and λ i represents the ratio of the maximum Z-axis displacement of the fin in the whole down (or up) stroke. The space asymmetry coefficient λ i is shown in Equation (10).…”
Section: Construction Of Cpg Phase Oscillatormentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it is defined as the pectoral fin flapping mode when the space asymmetry coefficient α i line R i is not equal to 0, and λ i represents the ratio of the maximum Z-axis displacement of the fin in the whole down (or up) stroke. The space asymmetry coefficient λ i is shown in Equation (10).…”
Section: Construction Of Cpg Phase Oscillatormentioning
confidence: 99%
“…It achieves self-excited oscillations through mutual inhibition between neurons, generating stable periodic signals that lead to the rhythmic movements of limbs and trunk positions. A few studies have examined the biologically inspired swimming control of robotic fish using CPG [9,10]. A CPG network based on the Hopf oscillator was used to control the robot fish Roman-ii, and the modes of forward, backward, turn, and switch between the modes were realized [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 20 ] found in their three-dimensional analysis that the pectoral fin changed the behavior of rotational motion when the pectoral fins performed an asymmetric motion on the left and right. The effects of the phase difference between the left and right pectoral fins on swimming in rays and manta rays have also been reported [ 21 , 22 ]. From this point, the hydrodynamic interaction between the pectoral fins and the body is considered to be working in the out-of-synchronized motion of the body and the pectoral fins, resulting in complex swimming of the fish.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Manta Ray Robot has fins actuated by an articulated mechanism actuated by two servomotors which recreate the curvature and the traveling wave on the fin [ 23 ]. The Manta Robot has three motors for each fin which give it excellent maneuverability thanks to the control algorithm based on phase oscillators [ 24 ]. Fins actuated by several mechanisms are also present in the Bionic Manta Ray Robot [ 25 ] and in the Robotic Manta [ 26 ].…”
Section: Introductionmentioning
confidence: 99%